Power analysis attack of dynamic password token based on SM3 - Zhi-bo DU; Zhen WU; Min WANG; Jin-tao RAO (Tongxin xuebao)
A novel method of the power analysis attack of dynamic password token based on SM3 was first proposed to choose the permutation function output as the power analysis attack target，and the simultaneous equations about the key were composed of the attack results.According to the given inverse permutation function,the key was derived by solving the simultaneous equations based on the inverse permutation function.Measured results are presented to validate the proposed method was effective.The proposed method solved the problems of permutation function keys for direct selection of target as an energy analysis attack target.And the proposed method can also be applied to the power analysis attack of the other cryptographic algorithms.